Proboscis lateralis- A 17 years follow-up, a case report - Vyas U; Raibagkar S; Vora H; Bhavsar D (Indian Journal of Plastic Surgery)
Proboscis lateralis is a rare congenital anomaly for which no embryological basis has been established. Besides heminasal aplasia or hypoplasia, various other craniofacial anomalies are also associated with it. It is only uncommonly free of other anomalies. Evaluation of a patient should include CT scan examination to look for growth of facial and skull bones. Reconstruction should start at an early age. Proboscis itself is the best option for heminose formation. Cartilaginous or bony support can be planned later in the late teens to give good aesthetic result.